Best Performing PhD Student Award (2024) - Koutinas, Michalis (My University, 2026)
The Ph.D. student Andonia Nicodemou of Dr Koutinas' group was awarded the Best Performing PhD Student Award (2024) by the Department of Chemical Engineering of CUT.
Keywords: Sciences